2012
DOI: 10.1037/a0025118
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of procedural justice among female offenders: Time does not heal all wounds.

Abstract: The current study examined the association between perceived procedural injustice of court experiences and emotional, attitudinal, and behavioral outcomes among 94 adolescent and young adult females incarcerated in a high security juvenile facility. Specifically, perceived injustice was related to background characteristics (e.g., race), as well as increased levels of depressive symptoms, institutional offending, and substance use within the facility. These negative effects of perceived injustice were most evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 93 publications
(106 reference statements)
6
44
0
Order By: Relevance
“…Likely because of the difficulties in gaining access to and surveying inmates (Pickett et al 2014), previous investigations have focused almost exclusively on either the general public or on minor offenders, such as persons stopped for traffic violations or tax offenders (Murphy 2004(Murphy 2005Tyler 2006). In addition, the existing studies that explore offenders' procedural justice perceptions have largely concentrated on male inmates' views about the staff and processes of correctional facilities (Beijersbergen et al 2014;Henderson et al 2010;Reisig & Me sko 2009) with fewer studies examining female offenders (Tatar et al 2012). We further develop this literature by examining female inmates' views about court procedural justice.…”
mentioning
confidence: 99%
“…Likely because of the difficulties in gaining access to and surveying inmates (Pickett et al 2014), previous investigations have focused almost exclusively on either the general public or on minor offenders, such as persons stopped for traffic violations or tax offenders (Murphy 2004(Murphy 2005Tyler 2006). In addition, the existing studies that explore offenders' procedural justice perceptions have largely concentrated on male inmates' views about the staff and processes of correctional facilities (Beijersbergen et al 2014;Henderson et al 2010;Reisig & Me sko 2009) with fewer studies examining female offenders (Tatar et al 2012). We further develop this literature by examining female inmates' views about court procedural justice.…”
mentioning
confidence: 99%
“… For recent studies on criminal offenders’ procedural justice perceptions of the police, criminal justice system, and the courts, see Baker et al ; Tatar II, Kaasa, and Cauffman .…”
mentioning
confidence: 99%
“…Procedural justice has also been shown to be effective among incarcerated offenders (Baker et al, 2013;Reisig & Mesko, 2009;Tatar et al, 2012). However, Augustyn (2015) argues that the impact of procedural justice among adults engaged in regular offending is weak compared to conventional non-offenders and that the effectiveness of procedural justice on youth offenders, while promising, remains inconclusive.…”
Section: Procedural Justice and Groups Engaged In Illegal Behaviourmentioning
confidence: 99%
“…Additionally, a study of domestic violence offenders found that offenders who perceived that their arresting police officers were procedurally just during their arrest had lower rates of re-offending post-arrest (Paternoster, Brame, & Sherman, 1997). A number of studies have also shown procedural justice to be effective among arrestees (White, Mulvey, & Dario, 2015) and incarcerated female offenders (Baker et al, 2013;Tatar, Kaasa, & Cauffman, 2012). However, it is unclear whether there are differences in the impact of procedural justice among offenders compared to the general population.…”
Section: Contact With Police and Perceptions Of Police And Policingmentioning
confidence: 99%
See 1 more Smart Citation